Background Pressure Induced Structural and Chemical Change in NiV/B4C Multilayers Prepared by Magnetron Sputtering - Wei, Zhenbo; Zhang, Zhe; Jiang, Li; Yang, Yang; Chang, Chenyuan; Feng, Yufei; Qi, Runze; Huang, Qiushi; Yan, Wensheng; Xie, Chun; Wang, Zhanshan (Frontiers in Physics, 2022)
NiV/B4C multilayers with small d-spacing are suitable for multilayer monochromator working at photon energy region from 5 to 8 keV, or photon energy region from 10 to hundred keV. To investigate the influence of background pressure during fabrication, NiV/B4C multilayers with a d-spacing of 3.0 nm were fabricated by magnetron sputtering with different background pressures. The grazing incidence X-ray reflectivity (GIXR) and transmission electron microscopy (TEM) measurement illustrated the structural change happened in NiV/B4C multilayers when background pressure is high. The electron dispersive X-ray spectroscopy (EDX) of NiV/B4C multilayer deposited with a high background pressure suggests a gradient distribution of oxygen which corresponding to the gradient thickness change. The detailed X-ray absorption near edge spectroscopy (XANES) comparison of NiV/B4C multilayers, NiV coating and B4C coating shown the chemical state change induced by background pressure. We concluded that during the deposition, vanadium oxidates promoted the oxidation of boron. In order to fabricate a good performance NiV/B4C multilayers, the background pressure needs lower than 1×10-4 Pa.